In-structure shock assessment of underground structures with consideration of rigid body motion - Ma, Guowei (2012)
The present study assesses the in-structure shock of an underground structure induced by a nearby subsurface detonation. Both the rigid body motion of the entirely buried structure and the local response of the structural element are considered in characterizing the in-structure shock. Soil-structure interaction, behaving as an interfacial damping, is taken into account, and the effect of different surrounding soils is investigated. A response spectrum is plotted for assessing in-structure shock induced by a typical subsurface detonation, and subsequently the safety of the internal facilities and equipment mounted on the buried structure is evaluated. For safety purposes, the protective structures are better constructed in a site with small acoustic impedance and a large attenuation factor. Results show that the proposed in-structure shock assessment method is effective and can be used as a supplement to TM-5-855-1 and TM-5-1300.